Does ‘Pesantren’ Environment have Impact on Islamic Entrepreneurial Intention? - Fitriana, Nita (UIN Fatmawati Sukarno Bengkulu, 2022)
This paper analyses Islamic entrepreneurial intention by involving college students in Yogyakarta as respondents. Two questions can be proposed: first, does the Pesantren environment influence Islamic entrepreneurial intention, and second, what are influencing factors on the improvement of Islamic entrepreneurial meaning. The research method used explanatory by using SEM-AMOS analysis. This study adopted the Islamic Entrepreneurial Intention model Theory of Planned Behavior, which was modified by Ashraf (Ashraf, 2021). The novelty of this research is by adding Pesantren environment as a variable independent. It was tested on Islamic entrepreneurial intention. This research shows that only self-efficacy and perceived social support factors influence entrepreneurial intention among five factors that influence students' entrepreneurial intention. The other three elements, namely prior experience, empathy, and moral obligation, do not influence Islamic entrepreneurial intention. On students, the category shows there is no difference in Islamic entrepreneurial intention between college students living in pesantren and college students not living in Pesantren. Pesantren environment is considered as less effective in performing its role in growing the student's intention who live in Pesantren to do Islamic entrepreneurship.